Comparison of minimally invasive versus conventional thoracic aortic operations: Early and midterm results in a series of 624 patients. Issue 12 (15th November 2022) - Berretta, Paolo; Chiuselli, Giulia; Galeazzi, Michele; Codecasa, Riccardo; Alfonsi, Jacopo; Braconi, Lucio; Bifulco, Olimpia; Rapisarda, Fabio; Malvindi, Pietro Giorgio; Bonacchi, Massimo; Stefano, Pierluigi; Di Eusanio, Marco
Abstract: Objective: Despite minimally invasive techniques having gained wider application in cardiac surgery, current evidence on minithoracic aortic surgery is still limited. The aim of this study was to compare early and midterm outcomes of patients undergoing operations of the proximal thoracic aorta through ministernotomy (MS) versus full sternotomy (FS). Methods: Data from 624 consecutive patients who underwent proximal aortic repair through MS ( n  = 214, 34.3%) and FS ( n  = 410, 65.7%) at two aortic centers were analyzed. Treatment selection bias was addressed using propensity score matching (MS vs. FS). After matching, two well‐balanced groups of 202 patients each were created. Results: Median cardiopulmonary bypass and cross‐clamp times were 88 and 68 min, respectively, with no difference between groups. Overall, 30‐day mortality was 1% ( n  = 2) in MS and 0.5% ( n  = 1) in FS ( p  = .6). No difference was found in the rates of stroke (MS n  = 5, 2.5%; FS n  = 5, 2.5%), dialysis (MS n  = 1, 0.5%; FS n  = 4, 2%), bleeding (MS n  = 7, 3.5%; FS n  = 7, 3.5%), and blood transfusions (MS n  = 67, 33.3%; FS n  = 57, 28.4%). Patients receiving MS showed a lower incidence of respiratory insufficiency compared with FS (0% vs. 2.5%, p  = .04). Intensive care unit and hospital stays were similar between groups. Two‐year survival rate was 97.2% in MS and 96.5% in FS ( p  = .9). Conclusions: Mini proximal aortic operations can be performed successfully without compromising the proven efficacy and safety of conventional access. In selected patients, MS was associated with very low mortality and morbidity rates. Additionally, MS demonstrated superior clinical outcomes as regards respiratory adverse events, when compared with FS.